2006
DOI: 10.1126/science.1125718
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectral Results of Asteroid Itokawa from the Hayabusa Spacecraft

Abstract: The near-infrared spectrometer on board the Japanese Hayabusa spacecraft found a variation of more than 10% in albedo and absorption band depth in the surface reflectance of asteroid 25143 Itokawa. Spectral shape over the 1-micrometer absorption band indicates that the surface of this body has an olivine-rich mineral assemblage potentially similar to that of LL5 or LL6 chondrites. Diversity in the physical condition of Itokawa's surface appears to be larger than for other S-type asteroids previously explored b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(95 citation statements)
references
References 21 publications
8
86
1
Order By: Relevance
“…This scenario is consistent with findings from the Hayabusa spacecraft data, which showed no significant difference in surface composition or regolith structure between the two lobes (Abe et al 2006a;Saito et al 2006). As discussed above, we have analysed this in detail and conclude that such a scenario can only realistically account for up to ∼5 m in the determined COM shift (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…This scenario is consistent with findings from the Hayabusa spacecraft data, which showed no significant difference in surface composition or regolith structure between the two lobes (Abe et al 2006a;Saito et al 2006). As discussed above, we have analysed this in detail and conclude that such a scenario can only realistically account for up to ∼5 m in the determined COM shift (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The recovered particles were carefully studied by the preliminary examination (PE) team, and the obtained results provide significant and unique information about the formation and evolution of meteorite parent bodies Nagao et al 2011;Nakamura et al 2011;Noguchi et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011). The mineral compositions and oxygen isotope ratios of the particles studied by the PE team are very similar to those of the equilibrated LL chondrites Yurimoto et al 2011), which match the spectroscopic observations by the Hayabusa spacecraft (e.g., Fujiwara et al 2006;Abe et al 2006;Okada et al 2006). These studies further suggested that Itokawa is made of reassembled fragments of the interior portions of a once larger asteroid at least 20 km in diameter (e.g., Nakamura et al 2011Nakamura et al , 2014 and thus represents only a small fraction of the original asteroid's mass.…”
Section: Introductionsupporting
confidence: 49%
“…Because our calibrations were derived entirely from ordinary chondrites, they should provide more accurate Fs compositions and may provide some insight into the partial melting debate. One example is the S-type asteroid Itokawa, which has identified as a possible partial melt based on FeO content (Fs 43±5 ) (Abell et al, 2007) and as an LL-chondrite parent body based on spectral parameters (Abe et al, 2006). Using spectral parameters measured by Thomas and Binzel (2009) (Brearley and Jones (1998) and references therein).…”
Section: Fig 2 Current Classification For S(iv)-type Asteroids Modimentioning
confidence: 99%